PERBEDAAN KUALITAS CITRA ANATOMI PADA PEMERIKSAAN MRI SHOULDER JOINT DENGAN MENGGUNAKAN SHOULDER COIL DAN FLEX COIL DI RUMAH SAKIT UNIVERSITAS HASANUDDIN - Syafitra, Muhnal; Astina, Kadek Yuda; Sugiantara, Aried (Medical Imaging and Radiation Protection Research Journal, 2023)
Background: Shoulder Joint MRI examination is one of the musculoskeletal examinations that is often carried out in the MRI modality because the Shoulder joint is one of the most active joints. In order to be able to visualize a good image, the right coil is needed, in the shoulder joint MRI examination it is recommended to use a shoulder array coil or shoulder coil. This examination can also use a flex coil in an MRI shoulder joint examination at the hospital if the congenital shoulder coil is damaged. The shoulder coil has better image quality because of its shape that surrounds the entire object you want to examine. Methods: This study used a quantitative approach with a quasi-experimental approach, namely conducting experiments on the observed objects, to find answers to the problems raised by conducting an MRI Shoulder Joint examination using two different types of coils, namely Shoulder coil and flex coil in 10 samples. The data is then processed using SPSS. Results and Conclusions: Based on the results of statistical test calculations for the SNR value of the anatomy of the shoulder joint, there is a significant difference in image quality, namely the SNR of the anatomy of the shoulder joint using shoulder coil and flex coil which has an overall p value/sig of 0.038 so that Ho is rejected and Ha is accepted. The average SNR for shoulder coil was 312.41 and flex coil was 246.30, so the difference in the SNR value for MRI shoulder joint using shoulder coil compared to flex coil was 66.11. With these results, the more optimal MRI Shoulder joint examination uses the Shoulder coil. Keywords: Shoulder Coil, Flex Coil, Signal to Noise Ratio (SNR)